2018
DOI: 10.1109/lra.2018.2798283
|View full text |Cite
|
Sign up to set email alerts
|

Graph SLAM Sparsification With Populated Topologies Using Factor Descent Optimization

Abstract: Abstract-Current solutions to the simultaneous localization and mapping (SLAM) problem approach it as the optimization of a graph of geometric constraints. Scalability is achieved by reducing the size of the graph, usually in two phases. First, some selected nodes in the graph are marginalized and then, the dense and non-relinearizable result is sparsified. The sparsified network has a new set of relinearizable factors and is an approximation to the original dense one. Sparsification is typically approached as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Mazuran et al [20] go one step further, proposing nonlinear factor recovery that allows to replace dense factors by arbitrarily defined "virtual" nonlinear measurements. Vallvé et al [33] propose a factor descent algorithm for belief sparsification. The recent work of [12] does not aim for a sparsification of the global pose graph, but for an efficient sparse approximation of the dense prior resulting from marginalization of the past measurement in sliding-window SLAM approaches.…”
Section: Related Workmentioning
confidence: 99%
“…Mazuran et al [20] go one step further, proposing nonlinear factor recovery that allows to replace dense factors by arbitrarily defined "virtual" nonlinear measurements. Vallvé et al [33] propose a factor descent algorithm for belief sparsification. The recent work of [12] does not aim for a sparsification of the global pose graph, but for an efficient sparse approximation of the dense prior resulting from marginalization of the past measurement in sliding-window SLAM approaches.…”
Section: Related Workmentioning
confidence: 99%
“…[Blanco et al 2008] used Bayesian filtering to provide a probabilistic estimation based on the reconstruction of the robot path in a hybrid discrete-continuous state space. [Vallvé et al 2018] proposed factor descent and non-cyclic factor descent, two simple algorithms for SLAM sparsification.…”
Section: Topological Slammentioning
confidence: 99%
“…In [1,14] we introduced factor descent optimization. Given a non-dense factor topology, factor descent iteratively optimizes each of the factors leaving fixed the rest.…”
Section: Introductionmentioning
confidence: 99%
“…Its nature can be taken into account in the whole sparsification process. Indeed, the generalized formulation introduced in [1], and completed in [14], is suited to pose-graph SLAM. We found that in such case, some conditions can not take place and the general formulation can be simplified.…”
Section: Introductionmentioning
confidence: 99%